2014
DOI: 10.1515/secm-2013-0185
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of aluminium matrix composites under thermal stresses

Abstract: The present review work elaborates the behaviour of aluminium matrix composites (AMCs) under various kinds of thermal stresses. AMCs find a number of applications such as automobile brake systems, cryostats, microprocessor lids, space structures, rocket turbine housing, and fan exit guide vanes in gas turbine engines. These applications require operation at varying temperature conditions ranging from high to cryogenic temperatures. The main objective of this paper was to understand the behaviour of AMCs during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 206 publications
0
11
0
Order By: Relevance
“…Whereas, the results from representative volume model delivered thermal conductivity values as 131 W/m⋅K, 126 W/m⋅K, 107 W/m⋅K and 76.9 W/m⋅K for Al‐ZC0, Al‐ZC1, Al‐ZC2, and Al‐ZC3 respectively. The deviation of simulated results from experimental results is ∼1.9 % for Al‐ZC0, ∼5.03 % for Al‐ZC1, ∼3.35 % for Al‐ZC2, and ∼1.75 % for Al‐ZC3.This discrepancy in simulated and experimental values is attributed to the phenomena like percolation present in the experimental specimens owing to inclusions touching each other, are extremely complicated to model while inclusion are in lower volume fraction [13, 14]. The lower coefficient of thermal expansion of ceramic particles than aluminium alloys may be the cause of this behaviour.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Whereas, the results from representative volume model delivered thermal conductivity values as 131 W/m⋅K, 126 W/m⋅K, 107 W/m⋅K and 76.9 W/m⋅K for Al‐ZC0, Al‐ZC1, Al‐ZC2, and Al‐ZC3 respectively. The deviation of simulated results from experimental results is ∼1.9 % for Al‐ZC0, ∼5.03 % for Al‐ZC1, ∼3.35 % for Al‐ZC2, and ∼1.75 % for Al‐ZC3.This discrepancy in simulated and experimental values is attributed to the phenomena like percolation present in the experimental specimens owing to inclusions touching each other, are extremely complicated to model while inclusion are in lower volume fraction [13, 14]. The lower coefficient of thermal expansion of ceramic particles than aluminium alloys may be the cause of this behaviour.…”
Section: Resultsmentioning
confidence: 89%
“…The increasing zirconia content in the aluminium 6061 matrix causes thermal conductivity to decrease, [13,14]. The lower coefficient of thermal expansion of ceramic particles than aluminium alloys may be the cause of this behaviour.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…In addition, this also reduces the thermal stress induced during heat treatment of sample. The authors [13,[17][18][19] reported that CTE mismatch is the reason for generation of thermal stresses during the composite fabrication, which can be minimised by controlled sintering temperature and the use of microwave sintering with SiC susceptors [20,21].…”
Section: Primary Processingmentioning
confidence: 99%
“…From this study, fine grain size, increase in tensile strength, increase in elongation and increase in hardness was observed in heat treated alloy. Khusbu Dash et al [13] studied the various thermal properties of aluminium matrix composite (AMC). The author concluded that thermal expansion mismatch and reinforcement volume in composite is the reason for generation of thermal stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling of stresses, defects, and, in consequence, damage of particle-reinforced composite materials induced by thermal loadings have been widely investigated, cf. [ 8 , 9 , 10 , 11 , 12 ]. Various approaches have been used in modeling of these phenomena.…”
Section: Introductionmentioning
confidence: 99%